Mutual Interaction and Integration of Music Culture of She and Han Nationalities into the Present - Xie, Huali (Música Hodie, 2023)
The purpose of this paper was to level determine of mutual interaction and integration of the musical culture of She and Han nationalities into modernity through the study and coding of folk songs from four China geographical regions using a new musical feature density map for machine music classification. The conducted simulations revealed that FIR-ELM is the best choice of the three classifiers analyzed as it is able to provide the highest classification accuracy. The findings of this study can be used as a basis for further research on the interaction and integration of the musical culture of these nationalities.